Digital Inclusion and the Elderly of the Pechiche Commune of the Santa Elena Canton - Leon-Valle, Benjamín Wilson; Reyes, Janet Aurora Tigrero; Pozo, Glenda Elizabeth Tomalá; Cobos-Alvarado, Edgar Fabian (Journal of Posthumanism, 2025)
Digital inclusion emerges as a mechanism to incorporate adults into the digital era , this term refers to the process of integration of population groups that are affected by digital divides to older adults. The objective of the research is to understand the use of digital platforms for digital inclusion in older adults of the Pechiche commune of the Santa Elena canton. The methodology used was quantitative with a descriptive approach. A Likert scale survey format was used for the data collection, directed to older adults of the selected community. The results indicated that there are factors that condition digital inclusion, among them, the presence of economic, generational and geographic factors, which cause limitations and repercussions in the digital literacy of older adults. Finally, actions to promote the digital inclusion of older adults are recommended.